Accountability and Legal Protection for Notaries in the Case of Deed of Change of Shareholding Company - Angelina, Michelle; Hoesin, Siti Hajati (Eduvest - Journal of Universal Studies, 2025)
A Company Amendment Deed is a legal document prepared by a notary to record decisions and significant changes within a company, ensuring these changes have a legal basis and are recognized. In practice, abuse can occur in creating this deed, such as notary favoritism towards one party or share transfers unknown to the rightful owner. Notaries are required to perform their duties in accordance with Law Number 2 of 2014, which amends Law Number 30 of 2004 on the Position of Notary. Their role in the documents is limited to recording information based on the wishes and details provided by the parties involved. In addition to their responsibilities, notaries have the right to legal protection. This research examines the case of PT Asia Pacific Mining Resources (APMR), where legal shareholders reported the unauthorized transfer of shares to unrelated parties and the inflation of shares in PT Aserra Mineralindo Investama (AMI) by five times. The study analyzes the liability of notaries if they are found guilty of causing harm through their deeds and the legal protection available if they are proven innocent and have acted in accordance with legal provisions.